2016
DOI: 10.3389/fmicb.2016.00015
|View full text |Cite
|
Sign up to set email alerts
|

Potentiating the Heat Inactivation of Escherichia coli O157:H7 in Ground Beef Patties by Natural Antimicrobials

Abstract: Escherichia coli O157: H7 (EHEC) is a major foodborne pathogen largely transmitted to humans through the consumption of undercooked ground beef. This study investigated the efficacy of two food-grade, plant-derived antimicrobials, namely rutin (RT), and resveratrol (RV) with or without chitosan (CH) in enhancing EHEC inactivation in undercooked hamburger patties. Further, the effect of aforementioned treatments on beef color and lipid oxidation was analyzed. Additionally, the deleterious effects of these antim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(15 citation statements)
references
References 40 publications
0
15
0
Order By: Relevance
“…Previous researchers also identified antioxidant activity of RE, reporting that compounds with phytoalexin origin such as RE are potent antioxidants (Gerszon et al, ; Gülçin, ; Iuga et al, ). No significant difference was observed between RE and control groups in TBARS value of ground beef patties based on the results of Surendran Nair et al (). Their result is inconsistent with the finding of this study.…”
Section: Resultsmentioning
confidence: 87%
See 2 more Smart Citations
“…Previous researchers also identified antioxidant activity of RE, reporting that compounds with phytoalexin origin such as RE are potent antioxidants (Gerszon et al, ; Gülçin, ; Iuga et al, ). No significant difference was observed between RE and control groups in TBARS value of ground beef patties based on the results of Surendran Nair et al (). Their result is inconsistent with the finding of this study.…”
Section: Resultsmentioning
confidence: 87%
“…They reported inhibiting E. coli by RE, mediated by site‐specific oxidative damage to the cell membrane as the primary event. Surendran Nair et al () showed potentiating the heat inactivation of E. coli O157:H7 in ground beef patties by RE (0.1 and 0.2%). They suggested RE to be used for increasing the thermal inactivation of EHEC in undercooked patties.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The addition of chitosan at a concentration of 0·01% (w/w) enhanced the thermal inactivation of E. coli O157:H7 (EHEC) in ground beef by 1·5 log (CFU per g) (Surendran Nair et al . ). Chitosan at a concentration of 0·1% (w/v) acted synergistically with pressure treatment of apple juice to inactivate E. coli (Kumar et al .…”
Section: Use Of Chitosan To Enhance the Efficacy Of Other Antimicrobimentioning
confidence: 97%
“…Application of commercial herb extract-containing products to STEC-inoculated beef trimmings, two rounds of grinding, and up to seven days’ refrigerated (4 °C) storage, produced reductions of 0.1 to 0.2 log 10 CFU/g in STEC numbers [ 14 ]. More recently, researchers reported that the application of 0.05% or 0.1% rutin, or 0.1% or 0.2% resveratrol, did not reduce E. coli O157:H7 in ground beef patties during refrigerated storage, but did enhance reductions of the pathogen upon subsequent cooking to an internal temperature of 65 °C [ 15 ]. The use of encapsulation strategies, such as surfactant micelles, has been described as providing opportunity for enhanced transport and delivery of entrapped compounds to foodborne microbes in both animal- and plant-based foods [ 16 , 17 , 18 ].…”
Section: Introductionmentioning
confidence: 99%